2015
DOI: 10.1002/chin.201506306
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Enediynes: Exploration of Microbial Genomics to Discover New Anticancer Drug Leads

Abstract: Review: 57 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…56−58 Comparison of known enediyne BGCs revealed that only a set of five genes is conserved in all clusters, encoding the enediyne PKS, a thioesterase, and three unknown proteins commonly referred to as SgcE, SgcE10, and SgcE3/E4/E5, respectively, based on the C-1027 BGC nomenclature. 57,58 Cluster 13 contains the minimal enediyne PKS cassette as MicB006_4939 (SgcE), MicB006_4940 to MicB006_4942 (SgcE3/E4/E5), and MicB006_4938 (SgcE10) (Table S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…56−58 Comparison of known enediyne BGCs revealed that only a set of five genes is conserved in all clusters, encoding the enediyne PKS, a thioesterase, and three unknown proteins commonly referred to as SgcE, SgcE10, and SgcE3/E4/E5, respectively, based on the C-1027 BGC nomenclature. 57,58 Cluster 13 contains the minimal enediyne PKS cassette as MicB006_4939 (SgcE), MicB006_4940 to MicB006_4942 (SgcE3/E4/E5), and MicB006_4938 (SgcE10) (Table S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…24 The bacterial strains were cultured overnight and diluted to 10 6 CFU/mL in Luria−Bertani (LB) broth. YPMs were dissolved in DMSO and serially diluted to 20 different concentrations (1,2,4,8,16,32,64,128,256, and 512 ng/mL; 1, 2, 4, 8, 16, 32, 64, 128, 256, and 512 pg/mL) using LB broth on a 96well plate. Vancomycin was dissolved in DMSO and serially diluted to 10 concentrations (0.03125−16 μg/mL) using LB broth on each 96well plate.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[6][7] Enediynes are the most cytotoxic small molecules known to date, and are very promising payloads in ADCs. 8 Calicheamicin, a 10-membered enediyne natural product, is used as the payload for Mylotarg and Besponsa for the treatment of acute myeloid leukemia or acute lymphoblastic leukemia, respectively. Another ADC consisting of an anthraquinone-fused enediyne, uncialamycin and an anti-mesothelin mAb, showed sub-nanomolar potency against mesothelin-positive lung cancer cell lines in vitro (IC 50 = 0.88 nM, H226 cell line).…”
mentioning
confidence: 99%
“…1 The enediynes are some of the most potent natural products in existence to date, with subnanomolar inhibitory concentrations (IC 50 s) against a broad panel of cancer cell lines. 3,6 Although too toxic for direct use as chemotherapeutic agents, the enediynes have proven highly efficacious for anticancer therapy when delivered using polymer-based or antibody-directed systems. NCS as a polymer drug conjugate (SMANCS) has been marketed since 1994 for the treatment of certain types of leukemia and hepatoma.…”
mentioning
confidence: 99%
“…Other ADCs using C-1027 (also known as lidamycin) 8 and UCM as payloads are currently in various stages of preclinical and clinical studies. 6 It is remarkable that four of the 12 known enediynes have been translated into clinical drugs or are in preclinical development, representing an extraordinary success rate of 33%.…”
mentioning
confidence: 99%